(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Vedic mathematics is an ancient Indian mathematical system, or a set of precise rules, that may be applied to any trigonometric, algebraic, arithmetic, or geometric problem. The technique is based on 16 Vedic sutras, which are a collection of word equations that explain the steps or reasoning involved in solving a variety of mathematical problems that are difficult and time consuming to answer using traditional methods. Beginning with the foundations of Vedic mathematics, such as the meaning of Vedic mathematics, this article examines mathematical operations using Vedic mathematics. The Vedas mathematics formulae are then presented with the aid of many examples, and may be utilized to execute a variety of mathematical operations like as subtraction, addition, division, and multiplication, among others. Vedic math is a basic mathematics, but it is a better method to do mathematics. It has a bright future ahead of it, and it will aid in learning mathematics in depth with clear explanations. Because it is now taught in all high schools and colleges.